Coupling and Decoupling of Diverse Molecular Units in Glycosciences - Witczak, Zbigniew J.; Bielski, Roman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This unique book covers the latest developments in coupling and decoupling of biomolecules containing functionalized carbohydrate components, being one of the first collections in this important area of applied medicinal chemistry. Connecting molecules, often referred as bio-conjugation, has become one of the most often performed procedures in modern medicinal chemistry. Sometimes, when the connected molecules are not useful anymore, they must be disconnected. The molecules that must be connected (coupled) may belong to both small and large molecules and include such constructs as glycoproteins, glycopeptides and glycans. In this work, more than 15 experts address a comprehensive range of potential and current uses of in vitro and in vivo bio-conjugation methodologies, leading to a variety of glycoconjugates. The analytical aspects of bio-conjugation are also here discussed. Medicinal and organic chemists from graduate level onwards will understand the appeal of this important book.
Synthesis of N-linked glycopeptides using convergent enzymatic glycosylation combined with SPPS.- Synthetic Antitumor Vaccines through Coupling of Mucin Glycopeptide Antigens to Proteins.- Recent Advances in the Stereochemical Outcome of Multi Component Reactions Involving Convertible Isocyanides.- Glycoconjugate-based inhibitors of Mycobacterium tuberculosis GlgE.- Selective Transformations of the Anomeric Centre in Water Using DMC and Derivatives -- [3,3]-Sigmatropic Rearrangement as a Powerful Synthetic Tool on Skeletal Modification of Unsaturated Sugars --  Recognition of thiols in coupling reactions to organic and carbohydrate acceptors.- Chemical approaches toward neurodegenerative disease prevention: the role of coupling sugars to phenolic biomolecular entities --  Probing for Trypanosoma cruzi cell surface glycobiomarkers for the diagnosis and follow-up of chemotherapy of Chagas disease --  Syntheses and Functions Glycosaminoglycan Mimicking Polymers.- Methodsfor the high resolution analysis of glycoconjugates.- Masking Strategies for the Bioorthogonal Release of Anticancer Glycosides.- Example of Sacrificial Unit Using Two Different Click Reactions in Coupling and Decoupling (CAD) Chemistry.- Increased efficacy of NKT cell adjuvanted peptide vaccines through chemical conjugation.
Keywords: Medicinal chemistry; Chemistry, Organic; Bioorganic chemistry; Biomaterials; Medicinal Chemistry; Organic Chemistry; Bioorganic Chemistry; Biomaterials